Football, Culture, Skill Development and Sport Coaching: Extending Ecological Approaches in Athlete Development Using the Skilled Intentionality Framework - Vaughan, James; Mallett, Clifford J.; Potrac, Paul; López-Felip, Maurici A.; Davids, Keith (Frontiers in Psychology, 2021)
In this paper, we extend ecological approaches and offer enhancements in athlete development by utilising the Skilled Intentionality Framework. A broad aim is to illustrate the extent to which social, cultural and historical aspects of life are embodied in the way football is played and the skills young footballers develop. Here, we contend that certain aspects of the world (i.e., environmental properties) are ‘weighted’ with social and cultural significance, ‘standing out’ to be more readily perceived and simultaneously acted upon when playing football. To comprehend how patterns of team coordination and athletic skill embody aspects of culture and context we outline the value-directedness of player-environment intentionality. We demonstrate that the values an individual can express are very much constrained by the character of the social institutions (i.e., football clubs) and the social order (i.e., form of life) in which people live. In particular, we illuminate the extent to which value-directedness can act as a constraint on the skill development of football players “for good or ill”. We achieve this goal by outlining key ecological and relational concepts that help illustrate the extent to which affordances are value-realising and intentionality is value-directed (exemplified, by footballers performing in a rondo/square/box). To enhance coaching practice, we offer: a) insights into markers of skilled intentionality, and b), the language of skilled intentions, as well as highlighting c), an additional principle of Non-linear Pedagogy: Shaping players intentions, or more precisely shaping the value-directedness of player-environment intentionality. We contend that, if sport practitioners do not skilfully attend to sociocultural constraints and shape the intentions of players within training environments and games, the social, cultural, and historic constraints of their environment will do so: constantly soliciting some affordances over others and directing skill development.